Impact of the COVID-19 pandemic on brain death detection in German hospitals: a state-wide analysis of health data - Daniela Schoene; Martin Roessler; Katharina Eder; Albrecht Günther; Konrad Pleul; Axel Rahmel; Kristian Barlinn (Neurological Research and Practice)
Abstract Background The low rate of organ donation in Germany has been linked to a deficit in the detection of patients with brain death (BD) in hospitals. It is unclear how crisis-related health system disruptions, such as the COVID-19 pandemic, affect this detection deficit. Methods Secondary data analysis of anonymized data from deceased patients with acute brain injury from Saxony, Saxony-Anhalt and Thuringia during the pre-pandemic and pandemic period (01/2019–12/2022). Pandemic phases were stratified according to the predominant SARS-CoV-2 variant. Logistic multilevel models were employed to assess outcomes including diagnosis of BD, deceased organ donations, missed cases with potential BD and organ donation-related interactions with the German Organ procurement organization. Models accounted for regional COVID-19 incidence and first-dose vaccination rates, as well as age, gender and types of brain injuries. Results A total of 11,100 deceased individuals from 136 hospitals were analyzed. An inverse association was observed between COVID-19 incidence and the determination of BD (adjusted odds ratio [aOR] 0.94, 95%CI [0.91; 0.97]; p < 0.001) as well as deceased organ donation (aOR 0.94, 95%CI [0.90; 0.98]; p = 0.001). When stratified by pandemic phases, this inverse association was evident for both BD determination (aOR 0.92, 95%CI [0.87; 0.99]; p = 0.02) and deceased organ donation (aOR 0.90, 95%CI [0.83; 0.97]; p = 0.01) during the initial wild-type phase. In the alpha phase, the association was observed only for BD determination (aOR 0.76, 95%CI [0.59; 0.98]; p = 0.03). No association was found in subsequent pandemic phases. Conclusion The initial impact on BD detection during the pandemic highlights the importance of the health system's adaptive capacity in times of crisis.